Dynamics of Kerr-like medium with two-mode intensity-dependent cavity fields - Singh, Sudha; Ooi, Chong Heng Raymond (IOP Publishing, 2018)
The dynamics of an effective two-level atom coupled to two-mode intensity-dependent quantized cavity fields via a ladder process in the presence of a Kerr medium has been investigated. Eigenfunctions and eigenvalues of the Hamiltonian of the interacting system have been obtained using a unitary transformation method. The cavity field statistics and non-classical properties are investigated numerically through second-order correlation functions. The effect of detuning and the Kerr medium on the non-classical features of the atom-field state has been analyzed. We find that the presence of Kerr non-linearity enhances the non-classical correlation between the correlated beams at short time intervals and increases antibunching at short time intervals. © 2018 Astro Ltd.